2015
DOI: 10.3892/mco.2015.708
|View full text |Cite
|
Sign up to set email alerts
|

Development of combined thymic carcinoma and thymoma in an extrathymic lesion during long follow-up for recurrent thymoma

Abstract: Abstract. The present study reported a rare case of combined thymic squamous cell carcinoma and thymoma exhibiting a mass on the left chest wall. The patient underwent thoracotomy for invasive thymoma 15 years previously, however, suffered a relapse in the left intrathoracic space. Radiotherapy, chemotherapy and partial resection, as secondary surgery for the intrathoracic mass, were performed. The histological findings in the resected specimens revealed type B3 thymoma. As the patient developed a left chest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These studies reported that the vascular invasion was a bad prognosis factor and that it needs to be integrated in the staging system [46,57,71]. The surgical resecability of thymic carcinomas has been reported in many studies [4][5][6]8 [22]. The extension of the surgical resection has also been considered as a prognostic factor especially when associated to a lymph node curettage [8,23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies reported that the vascular invasion was a bad prognosis factor and that it needs to be integrated in the staging system [46,57,71]. The surgical resecability of thymic carcinomas has been reported in many studies [4][5][6]8 [22]. The extension of the surgical resection has also been considered as a prognostic factor especially when associated to a lymph node curettage [8,23].…”
Section: Discussionmentioning
confidence: 99%
“…After a complete surgical resection, the utility of radiation therapy has been debated in the literature and was reported to have no effect on the global survival or the survival without progression [5,22,56,58]. For low grade tumors, some authors reported the role of radiation therapy following surgical resection in the decrease of loco regional recurrences and secondary localizations [6,9,28,36,54,61,62,66,80,92].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations